Hemopexin and HO-1 induction during acute colitis in mice is dependent on interleukin-22 - Ajayi, Ayodeji Samuel; Gerkins, Claire; Fragoso, Gabriela; Calvé, Annie; Santos, Manuela M. (Frontiers in Immunology, 2025)
IntroductionInflammatory bowel disease (IBD) is a chronic, relapsing inflammatory disorder of the gastrointestinal tract that frequently requires long-term immunosuppressive therapy, which increases the risk of infections and other complications. During active disease, intestinal bleeding is common and leads to the release of free luminal heme, a pro-inflammatory molecule that can disrupt mucosal integrity, fuel microbial dysbiosis, and amplify inflammation. Interleukin-22 (IL-22) plays a protective role in the gut by promoting epithelial barrier integrity and wound healing. More recently, IL-22 has been shown to induce hemopexin, a heme scavenger protein that limits heme availability and suppresses bacterial growth during systemic infections.MethodsHere we investigate the protective role of IL-22 and hemopexin in the context of colitis using the dextran sodium sulphate (DSS) acute colitis model in mice. Wild-type (Wt) and Il22ra1-/- mice were used to evaluate the effects of exogenous hemopexin and hemin treatments on colitis severity.ResultsIL-22 signaling was crucial for the induction of hemopexin in the colon, as Il22ra1-/- mice exhibited limited hemopexin induction and more severe colitis, which could be reversed by recombinant hemopexin administration. Additionally, hemin treatment, known to upregulate heme oxygenase-1 (HO-1), failed to show full protective effects in Il22ra1-/- mice, suggesting that IL-22 signaling contributes to the anti-inflammatory and antioxidant effects of hemin by inducing hemopexin and HO-1.DiscussionThese findings reveal a critical protective role for IL-22 by increasing the amount of hemopexin and HO-1 production in the colon, which could be part of a protective mechanism that mitigates DSS-induced colonic inflammation. Given its epithelial-specific and immunomodulatory activity, IL-22 represents a promising therapeutic approach for IBD. Furthermore, hemopexin itself may serve as an adjunct therapy during active disease.